2010
DOI: 10.1051/0004-6361/200912603
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of vertical kink waves in a solar coronal arcade loop by a periodic driver

Abstract: Aims. We study an oscillatory driver as a possible excitation mechanism of vertical kink loop oscillations in the ideal MHD regime. Methods. We consider a solar coronal magnetic arcade with a dense photospheric layer. The two-dimensional numerical model that we implement includes the effects of nonlinearity and line curvature on the excitation and attenuation of fast magnetosonic kink waves. We investigate the effects of a driven sinusoidal pressure pulse and compare it with the impulsive excitation by a press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…Ballai et al (2008) have found that kink oscillations generated by a harmonic driver have a dominant period belonging to that of the driver, while for a non-harmonic driver (modelling a shock wave) the generated oscillations are of natural periods only. Similar conclusions were reached in Selwa et al (2010), where the authors pointed out that in the case of an oscillatory driver with a given frequency, only a small subset of loops will start to oscillate, i.e. those whose typical period matches that of the driver.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Ballai et al (2008) have found that kink oscillations generated by a harmonic driver have a dominant period belonging to that of the driver, while for a non-harmonic driver (modelling a shock wave) the generated oscillations are of natural periods only. Similar conclusions were reached in Selwa et al (2010), where the authors pointed out that in the case of an oscillatory driver with a given frequency, only a small subset of loops will start to oscillate, i.e. those whose typical period matches that of the driver.…”
Section: Discussionsupporting
confidence: 68%
“…Standing kink oscillations can be excited by an impulsive, flare-generated driver (e.g. McLaughlin & Ofman 2008), by a periodic driver associated with a coronal wave (Ballai et al 2008;Selwa et al 2010), or directly from reconnection . Alternative mechanisms, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Aschwanden et al 1999;Verwichte et al 2004), while the source of excitation of the vertical oscillations remains unclear. They are usually explained by placing an external driver below the loop, by the reconnection process or by footpoint motion (Brady & Arber 2005;Gruszecki & Murawski 2008;Selwa et al 2010;White et al 2013). Subsonic siphon flows have also been proposed as a possible excitation mechanism (Ofman et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Hood et al 2005;McLaughlin et al 2011), vertical kink modes (e.g. Gruszecki et al 2006;Wasiljew & Murawski 2009;Selwa et al 2010), oscillations in active regions (e.g. McLaughlin & Ofman 2008;Selwa et al 2011;Pascoe et al 2009;Pascoe & De Moortel 2014), fine structuring (e.g.…”
Section: Introductionmentioning
confidence: 99%